Formação de jovens para o mundo do trabalho e cidadania: experiência teórica e prática por meio de projeto extensionista - Perez, Deivis [UNESP] (My University, 2013)
This paper presents the extension project Youth Empowerment for Work and Citizenship. It is a psychosocial and an educational activity focused on the care of impoverished youths, aged between 14-19, from Assis-SP. It aims to contribute to the cognitive, affective and social process of the participants. The extension activity has benefited the education of Psychology undergraduates students to the mediation in human development under nonformal education. The theoretical and methodological background is based on the cultural-historical psychology of Vigotski. The results obtained are: the establishment of partnerships between universities and state and local public organizations; the incorporation of innovative thematic in psychology curriculum course at UNESP; production of academic-scientific research about the experience of Psychologists in social educational area; and the participation of one hundred young people as well as their parents or legal guardians in the project.

Este artigo apresenta o projeto de extensão universitária nomeado Programa Formação de Jovens para o Mundo do Trabalho e Cidadania. Trata-se de atividade psicossocial e educacional dedicada ao atendimento de jovens empobrecidos, com idade entre 14 e 19 anos, de Assis-SP e região. O objetivo é contribuir com o processo de desenvolvimento cognitivo, afetivo e social dos participantes. A atividade extensionista tem favorecido, também, a formação de graduandos de Psicologia para a mediação do desenvolvimento humano realizada no âmbito da educação não formal. O referencial teórico-metodológico é a Psicologia Histórico-Cultural de Vigotski. O Programa apresenta como resultados o estabelecimento de parcerias entre a universidade e organizações públicas estaduais e municipais; a incorporação de temáticas inovadoras ao currículo de Psicologia da UNESPcâmpus Assis, a realização de pesquisa acadêmico-científica sobre experiência de trabalho socioeducacional de psicólogos e, por fim, registrou-se o atendimento de cem jovens e cem pais ou responsáveis no Programa.
Youth empowerment for work and citizenship: a theoretical and practical experience through a university extension project
Keywords: Youth education; World of work; Psychologist education; Education for citizenship; Educação de jovens; Mundo do trabalho; Formação de psicólogos; Educação para a cidadania